2013
DOI: 10.1371/journal.pone.0060142
|View full text |Cite
|
Sign up to set email alerts
|

Kras Gene Mutation and RASSF1A, FHIT and MGMT Gene Promoter Hypermethylation: Indicators of Tumor Staging and Metastasis in Adenocarcinomatous Sporadic Colorectal Cancer in Indian Population

Abstract: ObjectiveColorectal cancer (CRC) development involves underlying modifications at genetic/epigenetic level. This study evaluated the role of Kras gene mutation and RASSF1A, FHIT and MGMT gene promoter hypermethylation together/independently in sporadic CRC in Indian population and correlation with clinicopathological variables of the disease.MethodsOne hundred and twenty four consecutive surgically resected tissues (62 tumor and equal number of normal adjacent controls) of primary sporadic CRC were included an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 41 publications
2
40
1
4
Order By: Relevance
“…35 Also in this case, RASSF1A methylation levels varied with studies ranging from 10-20% of CRC subjects up to 40-50%, with some authors observing RASSF1A methylation in early stages of CRC, and others reporting it more frequently methylated in later stages. [35][36][37] Some correlations with tumor stage were also observed in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…35 Also in this case, RASSF1A methylation levels varied with studies ranging from 10-20% of CRC subjects up to 40-50%, with some authors observing RASSF1A methylation in early stages of CRC, and others reporting it more frequently methylated in later stages. [35][36][37] Some correlations with tumor stage were also observed in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Risk factors including red and processed meat consumption, obesity, physical inactivity, excessive smoking and alcohol consumption may significantly manipulate the causation of CRC (Giovannucci et al, 1995;Boyle et al, 2011;Jemal et al, 2011;Kim et al, 2011;Sinha et al, 2013). In our study, intake of fatty diet (60%), spicy food (45%) and non vegetarian diet (43%) were the most commonly observed lifestyle factors.…”
Section: Discussioncmentioning
confidence: 47%
“…At the molecular level, studies have clearly shown that genetic/ epigenetic changes may greatly affect the development of the disease transforming the epithelial cells into adenocarcinomas (Frank et al, 2010;Carvalho et al, 2012;Sinha et al, 2013;Farkas et al, 2014). Numerous signs and symptoms have been reported in patients presenting with CRC and a host of attributable factors have been found to play a significant role in the development of this disease.…”
Section: Discussioncmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, expression studies of Hippo pathway components in CRC have been reported by some groups [78,[82][83][84][85][86], however, only Liang et al presented complex data regarding collaborative expression analysis of the most important Hippo genes [87]. They found decreased mRNA ratios of LATS1 and MST1/2 as well as increased mRNA levels of YAP, TAZ, TEAD and OCT4 in CRC in comparison to healthy colon [87].…”
Section: The Role Of Hippo Pathway In Colorectal Cancermentioning
confidence: 99%